2017
DOI: 10.1002/ijgo.12206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its association with lifestyle and cardiovascular biomarkers among postmenopausal women in western Algeria

Abstract: Postmenopausal status could predict MetS, with inflammation and oxidative stress arising from an unhealthy lifestyle potentially increasing cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Evidence indicates that elevated body fat and hypertension are responsible for increased oxidative stress in elderly persons. 36,37 So far, it should be noted that, there have not been reports documenting healthy elderly persons only with insulin-resistance and higher damage oxidative marker (TBARS) which correlates negatively with age. Moreover, it is particularly interesting that our investigated elderly population had higher TBARS in insulin-sensitive ones.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that elevated body fat and hypertension are responsible for increased oxidative stress in elderly persons. 36,37 So far, it should be noted that, there have not been reports documenting healthy elderly persons only with insulin-resistance and higher damage oxidative marker (TBARS) which correlates negatively with age. Moreover, it is particularly interesting that our investigated elderly population had higher TBARS in insulin-sensitive ones.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our findings, these authors observed no differences in HDL, fasting glucose levels and hs-CRP. Prior reports from other populations have observed changes in lipid profiles and a high prevalence of metabolic syndrome among postmenopausal women [7]. The large study by Auro et al [27] found some lipid markers, including VLDL-c and LDL-c, to be predictors of menopause status.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a well-known risk factor for both CVD and cancer, being also more prevalent in postmenopausal women [46]. In this context, several biomarkers of metabolic risk have been evaluated in postmenopausal women, attempting to explain the epidemiologic connection between menopause and CVD [7]; however, laboratory findings observed remain widely controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is a result of aging, which essentially means that the ovaries are no longer ovulating or producing very few sex hormones [ 11 , 12 ]. Clinically, natural menopause is defined as a 1-year period of amenorrhea following the final menstrual period (FMP) without any pathological or physiological cause [ 13 , 14 ].…”
Section: Definition Of Menopause and Metabolic Disordersmentioning
confidence: 99%